1997
DOI: 10.1007/s11626-997-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication of a granulosis virus isolated from the potato tuber moth in a new established cell line of Phthorimaea operculella

Abstract: A newly established cell line was obtained from the culture of embryonic cells of the potato tuber moth Phthorimaea operculella in low temperature conditions (19 degrees C) using modified Grace's medium supplemented with 10% fetal bovine serum. The population doubling time was about 80 h when cells were cultivated at 19 degrees C and 38 h at 27 degrees C. The cell line had a relatively homogeneous population consisting of various sized spherical cells. The cells were cultivated for more than 25 passages. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
0
4
0
3
Order By: Relevance
“…Microbial Control Insect diseases caused by bacteria, viruses, and nematodes have been developed as microbial pesticides to control insect pests not only in the field but also in the storage (Reed 1969(Reed , 1971Reed and Springett 1971;Hunter 1973;Briese and Mende 1983;Alcázar et al 1992;BenSalah and Aalbu 1992;Das et al 1992;Kroschel et al 1996b;Lery et al 1997;Roux and Baumgartner 1998;Setiawati et al 1999). However, microbial control of P. operculella is not yet developed for massive commercial use although some authors have indicated the potential use of those pathogens in the future (Lacey and Arthurs 2005;Arthurs et al 2008).…”
Section: Parasitoids and Predatorsmentioning
confidence: 99%
“…Microbial Control Insect diseases caused by bacteria, viruses, and nematodes have been developed as microbial pesticides to control insect pests not only in the field but also in the storage (Reed 1969(Reed , 1971Reed and Springett 1971;Hunter 1973;Briese and Mende 1983;Alcázar et al 1992;BenSalah and Aalbu 1992;Das et al 1992;Kroschel et al 1996b;Lery et al 1997;Roux and Baumgartner 1998;Setiawati et al 1999). However, microbial control of P. operculella is not yet developed for massive commercial use although some authors have indicated the potential use of those pathogens in the future (Lacey and Arthurs 2005;Arthurs et al 2008).…”
Section: Parasitoids and Predatorsmentioning
confidence: 99%
“…Studies into these processes are facilitated by the availability of cultured cells that support the entire life cycle of the virus. For baculoviruses robust replication in cell culture has been achieved for NPVs infecting Lepidoptera (39,54,116,121) and to a limited extent for GVs (40,77,98,133). (30,32).…”
Section: Cellular Host-rangementioning
confidence: 99%
“…Six established lepidopteran cell lines were used in this study. Two cell lines obtained from embryonic cells of P. operculella, ORS-Pop-93 (Po93) (Léry et al, 1995) and ORS-Pop-95 (Po95) (Léry et al, 1997) were cultured in modified Grace's medium (Léry and Fédière, 1990) containing 10% fetal bovine serum (FBS). Po93 was maintained at 27 • C, and was routinely subcultured every 5 to 7 days when 1 to 2 × 10 6 cells were seeded in each 25 cm 2 flask.…”
Section: Established Cell Linesmentioning
confidence: 99%